Learning numbers to 20 - Sinclair, Karleen; Anderson, Greg; Heather, Warwick (Cairo Dar el farouk, 2004)
In this book , students will revise and writing numbers1 to 9, then focus on nuymbers 10 to 20 they will practise counting, writing and making groups of numbersto20
Mathematics
8 12 13
Keywords: Mathematics